Nilai-Nilai Kearifan Lokal Adat Sara Monda’u Sebagai Sumber Belajar Ilmu Pengetahuan Sosial - Fitriyani Saudi; Rahmawati Nurkarima (Jurnal Penelitian Pendidikan Geografi, 2024)
An effective way to introduce the local wisdom of a region to the younger generation is by making it a learning resource at school. This research aims to determine: 1) the local wisdom values ​​adhered to by the Sara Manda'u custom; 2) the social studies learning process at school; and 3) the values ​​of local wisdom of the Sara Manda'u tradition which are integrated into social studies subjects in Unaaha District, Konawe Regency. This research uses a qualitative method with a phenomenological approach. The results of this research show that: 1) the Sara Monda'u tradition has six local wisdom values, namely religious, social/mutual cooperation values, discipline values, educational values, environmental care values, and economic values; 2) the social studies learning process at SMPN 1 Unaaha and SMPN 2 Unaaha schools has significant differences, where SMPN 2 Unaaha students have better enthusiasm, infrastructure, teacher competence and learning outcomes; and 3) there are Sara Manda'u traditional local wisdom values ​​integrated into social studies subjects, namely: religion, discipline, responsibility, social care/mutual cooperation, and environmental care